Modulation of type I interferon induction by porcine reproductive and respiratory syndrome virus and degradation of CREB-binding protein by non-structural protein 1 in MARC-145 and HeLa cells - Kim, Oekyung (Virology, 2010)
Porcine reproductive and respiratory syndrome (PRRS) is an emerged disease of swine characterized by negligible response of type I IFNs and viral persistence. We show that the PRRSV non-structural protein 1 (Nsp1) is the viral component responsible for modulation of IFN response. Nsp1 blocked dsRNA-induced IRF3 and IFN promoter activities. Nsp1 did not block phosphorylation and nuclear translocation of IRF3 but inhibited IRF3 association with CREB-binding protein (CBP) in the nucleus. While IRF3 was stable, CBP was degraded, and CBP degradation was proteasome-dependent, suggesting that CBP degradation is not due to the protease activity of Nsp1 but an intermediary is involved. Our data suggest that the Nsp1-mediated CBP degradation inhibits the recruitment of CBP for enhanceosome assembly, leading to the block of IFN response. CBP degradation is a novel strategy for viral evasion from the host response, and Nsp1 may form a new class of viral antagonists for IFN modulation.